Limit analysis approach for accessing stability of three-dimensional (3-D) slopes reinforced with piles. Issue 7 (3rd October 2017) - Rao, Pingping; Zhao, Linxue; Chen, Qingsheng; Li, Lin
ABSTRACT: The stabilization of slopes by placing piles is one of the most innovative and effective slope reinforcement techniques in the coastal engineering in recent years. Due to the simplicity and efficiency, limit analysis method is the most common approach for assessing the stability of slopes. However, the majority of existing limit analysis methods is limited to slope without the presence of piles. In this technical note, a novel upper-bound limit analysis method was proposed to access the stability of three-dimensional slopes reinforced with piles incorporating the admissible rotational failure mechanism where toe failure, face failure, and base failure were taken into account. The effects of key designing parameters, e.g., pile location, pile spacing, slope angle, slope width on the stability of earth slopes, and geometry of critical slip surface were presented and discussed. The results demonstrate that the proposed approach is more appropriate for assessing the stability of slopes reinforced with piles and can be also utilized in the design of piles stabilizing the unstable slopes.